A calix[4]resorcinarene-based giant coordination cage: controlled assembly and iodine uptake. Issue 16 (31st January 2020) - Pei, Wen-Yuan; Yang, Jin; Wu, Hui; Zhou, Wei; Yang, Ying-Wei; Ma, Jian-Fang
Abstract : A giant calix[4]resorcinarene-based coordination cage, featuring efficient volatile iodine uptakes, was designed by tuning the ancillary ligand. Abstract : Construction of large multi-component coordination cages becomes much more challenging as the number of building blocks increases. A giant hexameric calix[4]resorcinarene-based coordination cage (cage-1 ) was successfully designed through the precise tuning of ancillary rigid tetracarboxylic acid. Significantly, cage-1 exhibited reversible uptake of volatile iodine, suggesting that it could serve as a porous material for efficient capture and separation of radioactive iodine.